Praktik Pemerintahan Desa dalam Penerapan Prinsip Good Governance di Desa Ciawigajah - Rifal Faliansyah; Harmono (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the implementation of Good governance principles in the governance of Ciawigajah Village, Beber District, Cirebon Regency and examine the obstacles and solutions to its implementation from a legal perspective. The research method used is empirical juridical with a statutory regulatory approach and field studies through interviews. The results of the study indicate that the principles of participation, transparency, accountability, effectiveness and legal certainty have been implemented, but are not optimal due to limitations in the quality of community participation, access to information, apparatus competence and public communication related to village fund management. Strengthening apparatus capacity, substantive transparency and participatory oversight are needed to realize good village governance.